2023
DOI: 10.1039/d2sc04862k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabright AIEdots with tunable narrow emission for multiplexed fluorescence imaging

Abstract: AIEdots with high brightness and narrow emission bandwidth were developed for multiplexed in vitro and in vivo fluorescence imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…However, the fluorescence of the as‐designed fluorophores with a relatively weak push–pull effect (TPE‐BT and all of the BTr‐contained fluorophores) was insensitive to the polarity change of the solvents. These results indicated that the as‐designed fluorophores containing strong electron‐withdrawing groups (DCPP, Figure 1a–d; Figures S14–S17, Supporting Information) or strong electron‐donating groups (tDPA, TPA and OTPA, Figure 1f–h; Figures S18, S19, Supporting Information) [ 35 ] showed stronger ICT effect than that of the fluorophores containing groups (BTr and TPE) with weak electron‐withdrawing or electron‐donating capacity (Figure 1e,i–l; Figures S20–S23, Supporting Information), which was consistent with the above theoretical calculation results. Their emission band tended to redshift and the fluorescence intensity decreased, respectively, with the increasing polarity of the solvent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fluorescence of the as‐designed fluorophores with a relatively weak push–pull effect (TPE‐BT and all of the BTr‐contained fluorophores) was insensitive to the polarity change of the solvents. These results indicated that the as‐designed fluorophores containing strong electron‐withdrawing groups (DCPP, Figure 1a–d; Figures S14–S17, Supporting Information) or strong electron‐donating groups (tDPA, TPA and OTPA, Figure 1f–h; Figures S18, S19, Supporting Information) [ 35 ] showed stronger ICT effect than that of the fluorophores containing groups (BTr and TPE) with weak electron‐withdrawing or electron‐donating capacity (Figure 1e,i–l; Figures S20–S23, Supporting Information), which was consistent with the above theoretical calculation results. Their emission band tended to redshift and the fluorescence intensity decreased, respectively, with the increasing polarity of the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…All of these as‐designed fluorophores exhibited an obvious solvatochromic fluorescence in different solvents (Figures S14–S23, Supporting Information) and displayed high fluorescence quantum yields (QY, ranging from 30–95%) in nonpolar solvents (Table S2, Supporting Information). [ 35 ] Meanwhile, the fluorophores featured with strong push–pull electron effect (all of the DCPP‐contained fluorophores, tDPA‐BT, TPA‐BT, and OTPA‐BT) tended to display a sharper fluorescence spectral change in response to the change of solvent polarity. However, the fluorescence of the as‐designed fluorophores with a relatively weak push–pull effect (TPE‐BT and all of the BTr‐contained fluorophores) was insensitive to the polarity change of the solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Another consideration for applications is bandwidth. Narrow bandwidth is preferred for high purity (e.g., organic light-emitting diodes) and selectivity (e.g., multiplexed imaging) . While π-conjugated organic chromophores tend to have significantly higher ε λ (a couple of orders magnitude higher), their bandwidth is generally broader compared to metal-centered emission (e.g., lanthanides) .…”
Section: Introductionmentioning
confidence: 99%
“…Narrow bandwidth is preferred for high purity (e.g., organic light-emitting diodes) and selectivity (e.g., multiplexed imaging). 14 While πconjugated organic chromophores tend to have significantly higher ε λ (a couple of orders magnitude higher), their bandwidth is generally broader compared to metal-centered emission (e.g., lanthanides). 15 Therefore, there is a strong push to develop narrowband organic emitters, 16 and with such molecules, one can realize the full potential of CPL-active organic chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…5 This inherent property of AIEgens enables their utilization in the fabrication of high-brightness organic nanoprobes through the augmentation of doping ratios for the luminescent centers within AIEgens-doped nanoparticles. 6 Regrettably, due to the predominance of conjugated D–A (donor–acceptor)-type structures with strong push–pull electron effects and poor water solubility among NIR-II AIEgens, their emission in polar solvents such as water is always accompanied by TICT (twisted intramolecular charge transfer) state emission and significant fluorescence quenching compared to their nonpolar solvent counterparts. To facilitate the biological applications of water-fast NIR-II AIEgens, they are typically encapsulated within nanoparticles composed of amphiphilic molecules such as F-127, DSPE-PEG, and proteins.…”
mentioning
confidence: 99%